Modern view of the problem of missed abortion - M. V. Andreeva; E. P. Shevtsova; K. O. Zabolotneva; E. D. Lyutaya; T. S. Sivko (Медицинский вестник Юга России, 2021)
Non-developing pregnancy is an urgent obstetric problem, which is included in the structure of reproductive losses and. The authors performed a systematic analysis of the data presented in the modern scientifi c literature on the epidemiology, etiology, pathogenesis, and diagnosis of non-developing pregnancy. Th e review includes data from foreign and domestic articles on this topic found in PubMed over the past 7 years.